IMPLEMENTASI WEBSITE SEBAGAI MEDIA INFORMASI DAN PROMOSI PADA PONDOK PESANTREN PUTRA-PUTRI ADDAINURIYAH 2 SEMARANG - Andik Prakasa Hadi; Faiz Abdul Rokhman (STEKOM PRESS, 2020)
Pondok Pesantren is a non-formal institution that is engaged in religious education. Pesantren is one of the places of education and preaching that is required to be able to provide information about Islam to the wider community. Easy access to information and communication, can be used to introduce pesantren to the public. Promotion using video profiles, brochures and banners has not been able to provide as much information as possible to the public, causing the pesantren to be less well known to the public. This research, in general, aims to promote and provide the widest possible information about Pondok Pesantren Addainuriyah 2 and its activities to the public through the website. In particular, it makes it easy for the public to access information and communicate intensively with administrators of the Addainuriyah 2 Semarang Islamic boarding school. The research method in this study is based on the suitability and type of research, using the Research and Development (R&D) method. R&D in education is often called research-based development. As a result of this research, the implementation of the website as a media of promotion and information in the Addainuriyah 2 Semarang Islamic boarding school, can provide a lot of information to the public, and as a means of communication between the general public and administrators of Pondok Pesantren Addainuriyah 2 Semarang.